Analysis for Friction Heating Power of Non-lubricated Auxiliary Bearing of Electromagnetic Bearing during Rotor Drop - LIU Xingnan1, 2, 3, , CHEN Guohui4, WANG Mingqi1, 2, 3, SHI Zhengang1, 2, 3, MO Ni1, 2, 3, , (Yuanzineng kexue jishu, 2024)
In order to predict the life of the auxiliary bearing in the design stage, it is crucial to calculate the friction heating power of the auxiliary bearing during the rotor drop process. In many cases, the auxiliary bearing has no lubrication or only solid lubrication. Therefore, the local method was chosen to calculate the friction power, focusing on analyzing the rolling elastic hysteresis power between the ball and raceway, the spin power of the ball and the differential sliding power between the ball and raceway. The calculation formulas of these powers were provided in this paper, along with the derivation of an analytical formula for the differential sliding power, which facilitates practical applications. These formulas are based on the quasi-static analysis and the raceway control theory. When the rotation speed of the inner ring of the auxiliary bearing, the radial force acting on the auxiliary bearing and the axial preloading force are all known, the friction heating power of the auxiliary bearing can be calculated by these formulas. The free drop experiment of an electromagnetic bearing high-speed motor without braking was carried out to test the calculation, under 3 000, 5 400, and 6 600 r/min. The rotor axis trajectory and the horizontal and vertical impact force acting on the auxiliary bearing were measured. The rotation speed of the inner ring of the auxiliary bearing was assumed to be the same as the speed of the rotor, calculated by the rotor axis trajectory. The radial force acting on the auxiliary bearing was calculated based on the horizontal and vertical impact force. The axial preloading force, which is about 410 N in this paper, was determined by the experimental data under 3 000 r/min with the method of trial calculation. With these parameters, the friction heating power of the auxiliary bearing was calculated, and compared with the change rate of the kinetic energy of the rotor observed in the experiment. It is found that the heating power calculated by the local method is approximately equivalent to the change rate of the kinetic energy, which proves the feasibility of the theoretical calculation. During the drop process of a non-lubricated auxiliary bearing, the spin of the ball generates the most heat, followed by the differential sliding between the ball and the raceway. The sum of the two accounts for the main part of the total heat, and the rolling elastic hysteresis between the ball and the raceway generates less heat.